Effectiveness of Training in Different Natural Environments on Some Biomechanical Variables of Sprint Runners in (100m, 200m, 400m) Events - Al-Saadi, Eman Sabeeh Hussein; Shalash, Maher Jaafar Ameen (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. Sprint events (100m, 200m, 400m) are high-performance athletic activities that rely on coordinated movement transfer governed by specific mechanical principles. Researchers have continually sought to identify the most effective training methods to enhance the performance of sprinters. The study’s research problem is centered on determining the effectiveness of training in different natural environments (dense grass, soft sand, and hard soil) and identifying which training surface is most beneficial for improving selected biomechanical variables in sprinters. Materials and method. The study aimed to examine the impact of training in different natural environments (excluding tartan tracks) and to determine which surface yields the most significant improvements for sprint runners. To achieve this, the researchers implemented an eight-week training program with two training sessions per week, using consistent sprint distances across all surfaces (10m, 20m, 30m, 40m, and 50m). The research sample consisted of 18 sprinters specializing in sprint events, divided into three equal groups: six for the 100m, six for the 200m, and six for the 400m. These athletes were in the specialized preparation phase and had participated in the first round of the Iraqi Clubs Championship in Sulaymaniyah on March 15, 2024, in preparation for the third round scheduled for October 20, 2024, in the same location. Results. The researchers analyzed four biomechanical variables: time, velocity, stride length, and stride frequency. These variables were measured over a 50-meter flying start using five perpendicular motion-analysis cameras positioned every 10 meters. The statistical method used was analysis of variance (ANOVA) to determine which training surface had the greatest impact on performance. Cunclotions. The study concluded that training on soft sand had a statistically significant effect, while the other surfaces did not show significant improvements. The researchers recommended conducting similar studies on different athlete categories and other athletic events.